Influence of Erosive and Abrasive Cycling on Bonding of Diferent Adhesive Systems Enamel: An in situ study - Ciccone Giacomini,Marina (2016)
This study evaluated the impact of orange juice on the bond strength (BS) of dentin bonding systems (DBSs) to enamel surface after simulation with an in situ/ ex vivo erosive cycling. One hundred and ninety two bovine enamel fragments (4x4x2 mm) were obtained and randomized regarding superficial microhardness and distributed to palatal devices for 8 volunteers, in three phases (one for each DBS), containing 8 blocks, which were, allocated in 4 pairs. Daily, these pairs were subjected extraorally to the following conditions: CONTneither erosive nor abrasive challenge; ERO- erosive challenge only; ABR- abrasive challenge only and ERO + ABR- with erosive and abrasive challenges. Erosive cycles (immersion in orange juice, 3 times/day/5 min/5 days) or/and abrasive challenges (electric toothbrush, 3 times/day/1 min/5 days) were performed. After these cycles, all specimens were restored with the adhesive systems Adper Scotchbond Multi Purpose (MP), Adper Single Bond 2 (SB) or Clearfil SE Bond (SE), and the composite resin Filtek Z250. After 7 days, sticks (area ≅1 mm2) were obtained and subjected to the microtensile bond strength test (μTBS) at 0.5 mm/min. Data was statistically analyzed by ANOVA and Tukey tests (a=0.05). Failure modes were determined using a digital microscope (40×). DBS was the only statistical significant factor. SE was the unique DBS not affected in any challenge, whereas MP and SB performed according to the scenario. The adhesive and mixed failures were predominant in all groups. Overall performance suggested that BS to enamel after erosive /abrasive challenged by orange juice was not affected and it was material-dependent